Alumina MTCC green sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202611097279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-23
AI Technical Summary
现有技术中尚未见针对氧化铝陶瓷、兼顾低温致密烧结与铜基浆料共烧兼容性的有效解决方案
(1)突破低温烧结强度瓶颈。本发明通过优化MTCC粉体配方,特别是对氧化铝粉体规格及烧结助剂组成、比例进行系统调整,使生瓷片在显著低于HTCC工艺的温度下即可实现致密烧结,抗弯强度获得大幅提升,较常规中温烧结助剂方案具有明显优势,在降低烧结温度的同时保证了材料的力学可靠性,满足多层陶瓷管壳对结构承载能力的实际需求。
Smart Images

Figure CN122586528B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials, specifically to an alumina MTCC green ceramic sheet and its preparation method. Background Technology
[0002] Alumina ceramic substrates are widely used in high-density electronic packaging due to their excellent mechanical properties, good insulation, and chemical stability. High-temperature co-fired multilayer ceramic (HTCC) technology, as one of the mainstream processes, achieves multilayer interconnect structures by co-firing high-melting-point metal pastes such as tungsten and molybdenum with alumina green ceramic tapes at high temperatures. However, because copper and its alloys have low melting points, they cannot withstand the high-temperature sintering environment of HTCC. Existing technologies can only use high-melting-point metals such as tungsten and molybdenum, which have relatively poor conductivity, as conductor materials. This results in generally high sheet resistance in metallized circuits, significant conductor losses, and heat generation problems, making it difficult to meet the growing demands of modern electronic devices for high current carrying capacity and high-frequency, low-loss transmission. Therefore, developing an alumina ceramic material that can be co-fired with highly conductive copper-based pastes has become an urgent technical challenge in this field.
[0003] To introduce copper-based pastes, a feasible approach is to lower the sintering temperature of alumina ceramics. Existing technologies have made some progress in reducing the sintering temperature of alumina by adding sintering aids, but most existing aid systems are designed for high-temperature co-firing processes above 1500℃. When attempting to further lower the sintering temperature to achieve co-firing with copper-based pastes, insufficient densification and significant deterioration of mechanical properties are often encountered, making it difficult to meet the structural strength and reliability requirements of packaging substrates. For example, Chinese patent CN107188568A relates to the tape casting of aluminum nitride ceramics, whose material system and sintering aids are fundamentally different from alumina-based ceramics; Chinese patent CN108033785A discloses a low-temperature sintering high-dielectric microwave dielectric ceramic, but it is based on a copper-niobium titanate system, which differs significantly from alumina ceramics in composition and performance requirements. Currently, there is no effective solution for alumina ceramics that balances low-temperature densification sintering with compatibility with copper-based paste co-firing.
[0004] To address the shortcomings of the existing technology, this invention provides an alumina medium-temperature co-fired ceramic (MTCC) green ceramic sheet and its preparation method. This invention utilizes a specific multi-component composite sintering aid system to enable the alumina green ceramic sheet to achieve dense sintering at a temperature significantly lower than that of the HTCC process, while maintaining good mechanical and dielectric properties. More importantly, this low-temperature sintering characteristic allows the alumina substrate to be co-fired with highly conductive copper-based conductor paste, thereby overcoming the inherent defect of high conductor loss in the traditional HTCC process. This provides a novel substrate material with both high reliability and excellent electrical performance for high-frequency, high-power electronic packaging. Summary of the Invention
[0005] In view of this, the present invention provides an alumina MTCC green ceramic sheet and its preparation method. By designing a specific multi-component composite sintering aid system, the alumina green ceramic sheet can achieve dense sintering at a temperature significantly lower than that of the HTCC process.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention discloses an alumina MTCC green ceramic sheet, wherein the inorganic ceramic powder of the green ceramic sheet is composed of alumina powder and sintering aids; the sintering aids include SiO2, TiO2, kaolin, CaO, NiO, ZrO2, Cr2O3 and Y2O3; the sintering aids account for 8% to 12% of the total mass of the inorganic ceramic powder.
[0007] As a further aspect of the present invention: the components in the sintering aid, by mass percentage, are as follows: SiO2 15%~17%, TiO2 3%~6%, Kaolin 20%–25%, CaO 16%~20%, NiO 9%~15%, ZrO2 8%~11%, Cr2O3 6%~11%, Y2O 36%~10%.
[0008] All components are in powder form, with SiO2 having a particle size of 1~4μm, kaolin having a particle size of 2~5μm, and the remaining components having a particle size of 1~3μm.
[0009] As a further aspect of the present invention: the purity of the alumina powder is ≥99.9%, and the average particle size is 0.5~1μm.
[0010] As a further aspect of the present invention: it is obtained by casting the inorganic ceramic powder and an organic carrier; the organic carrier includes a solvent, a binder, a plasticizer, and a dispersant; in the casting slurry, the mass percentage of the inorganic ceramic powder is 50% to 60%, the mass percentage of the binder is 5% to 10%, the mass percentage of the solvent is 30% to 40%, the mass percentage of the dispersant is 0.5% to 1%, and the mass percentage of the plasticizer is 1% to 3%.
[0011] As a further aspect of the present invention: the binder is polyvinyl butyral, the solvent is a mixture of anhydrous ethanol and methyl ethyl ketone, the dispersant is herring oil or Span 80, and the plasticizer is dibutyl phthalate.
[0012] Secondly, the present invention discloses an alumina medium-temperature co-fired ceramic substrate, which is obtained by sintering the above-mentioned alumina medium-temperature co-fired ceramic green ceramic sheet at 1400-1450°C.
[0013] As a further aspect of the present invention: the substrate has a bending strength ≥400MPa, a dielectric constant of 7.0~7.5, and a dielectric loss ≤0.003.
[0014] As a further aspect of the present invention: the substrate is co-fired with the tungsten copper conductor paste, and the sheet resistance of the metallized circuit is ≤7mΩ / □.
[0015] Thirdly, this invention discloses a method for preparing alumina medium-temperature co-fired ceramic green ceramic sheets, comprising the following steps: (1) Weigh SiO2, TiO2, kaolin, CaO, NiO, ZrO2, Cr2O3 and Y2O3, mix them and add anhydrous ethanol, grind and dry to obtain sintering aid powder, and control its D50 to 0.5~1.0μm after ball milling; (2) The sintering aid powder is mixed with alumina powder to obtain the inorganic ceramic powder; (3) The inorganic ceramic powder is mixed and ground with the solvent and dispersant, and then the binder and plasticizer are added and ground again to obtain the casting slurry; the solid content of the casting slurry is 50% to 60%; (4) After degassing the cast slurry, it is cast and dried to obtain the alumina medium-temperature co-fired ceramic green ceramic sheet.
[0016] This invention resolves the contradiction between low-temperature sintering and mechanical properties. The pure-phase sintering temperature of alumina ceramics is relatively high. Although adding conventional sintering aids can reduce the sintering temperature to within the acceptable range of the HTCC process, when attempting to further reduce the sintering temperature to meet the requirements of co-firing with specific conductor pastes, the densification process is significantly inhibited, and the bending strength decreases significantly, making it difficult to meet the requirements of multilayer ceramic tube shells for the mechanical reliability of the matrix.
[0017] Traditional HTCC (High-Temperature Hydrocarbon Ceramic) processes involve high sintering temperatures, making it impossible to directly co-fire copper-containing conductor pastes. Due to copper's low melting point, the copper phase undergoes significant melting and loss under the high-temperature sintering conditions of HTCC, failing to form a continuous and effective conductive path. Therefore, existing technologies have had to use high-melting-point metals such as tungsten and molybdenum as conductor materials, resulting in high sheet resistance and increased conductor losses, thus limiting the performance of devices in high-frequency, high-power applications. The goal is to reduce the sintering temperature and introduce low sheet resistance conductors while simultaneously maintaining the high flexural strength, excellent dielectric properties, and stable process compatibility of alumina ceramics, avoiding sacrificing the intrinsic advantages of the material due to adjustments in sintering aids or co-firing matching.
[0018] Compared with the prior art, the beneficial effects of the present invention are: (1) Breakthrough in low-temperature sintering strength bottleneck. This invention optimizes the MTCC powder formulation, especially by systematically adjusting the alumina powder specifications and the composition and proportion of sintering aids, so that green ceramic sheets can achieve dense sintering at a temperature significantly lower than that of the HTCC process, resulting in a significant improvement in flexural strength. This has obvious advantages over conventional medium-temperature sintering aid schemes, and ensures the mechanical reliability of the material while reducing the sintering temperature, thus meeting the actual requirements of multilayer ceramic tube shells for structural load-bearing capacity.
[0019] (2) Achieving low-temperature co-firing of tungsten-copper paste significantly reduces sheet resistance. Because the green ceramic sheet of this invention has low-temperature sintering characteristics, it can achieve good matching and co-firing with tungsten-copper conductor paste. Under optimized co-firing process conditions, the tungsten skeleton maintains structural integrity, and the copper phase is fully filled and densified. This avoids copper melting and loss, and significantly reduces the sheet resistance of the metallized circuit, by more than half compared to traditional HTCC. This effectively reduces conductor loss and heat generation, providing key technical support for high-frequency, low-loss packaging.
[0020] (3) While achieving high strength and low sheet resistance at low temperature, the sintered body of the present invention still maintains the excellent dielectric properties inherent in alumina ceramics. The dielectric constant is stable and the dielectric loss is low, which can meet the strict requirements of low delay and low signal attenuation for high-frequency microwave devices and system-level packaging.
[0021] (4) The alumina MTCC green ceramic sheet of the present invention is prepared by mature processes such as casting molding. The green ceramic sheet has uniform thickness and good flexibility, and is suitable for standardized processing procedures such as drilling, filling, precision printing, lamination and multi-layer co-firing. Its low-temperature co-firing and low sheet resistance characteristics make it expected to replace some traditional HTCC products in communication base stations, radio frequency modules, high-density packaging and other fields, and promote the development of devices towards higher frequency, higher reliability and lower power consumption. Attached Figure Description
[0022] Figure 1 This is a photograph of the overall appearance of the substrate after co-firing the alumina MTCC green ceramic sheet and tungsten copper paste obtained in Example 1 of the present invention. As shown in the figure, the substrate surface is flat and without warping, the printed tungsten copper conductor pattern has clear and sharp edges, and the lines are continuous and complete. There is no copper melting overflow, broken lines or balling, indicating that low-temperature co-firing below 1450 °C effectively inhibits copper loss. Figure 2 for Figure 1 A magnified micrograph of a portion of the conductor line. As shown in the figure, the internal structure of the tungsten-copper metallization layer is dense and uniform, without continuous pores or cracks; the interface between the metallization layer and the ceramic substrate is tightly bonded, without delamination or micro-gaps, demonstrating good co-firing compatibility and metallurgical bonding quality.
[0023] Figure 3The image shows a SEM micrograph of the substrate surface prepared in Example 1 of this invention. As can be seen from the image, the substrate consists of a large number of tightly packed polygonal grains, resulting in a dense structure. The grain size is concentrated between 2 and 5 μm. This microstructure indicates that the ceramic substrate is fully sintered and has good density, which is beneficial for obtaining excellent mechanical properties. Detailed Implementation
[0024] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0026] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional methods in the prior art, and therefore will not be described in detail; unless otherwise specified, the parts in the following embodiments refer to parts by weight.
[0027] Example 1 (1) Preparation of sintering aid: Weigh 16 parts SiO2, 5 parts TiO2, 23 parts kaolin, 16 parts CaO, 12 parts NiO, 10 parts ZrO2, 10 parts Cr2O3, and 8 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0028] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0029] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0030] (4) Casting, Lamination, Printing and Co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are laminated, isostatically pressed, and cut, and then tungsten copper conductor paste is printed using screen printing technology. Co-firing is carried out in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained (e.g., Figure 1 (As shown).
[0031] (5) Performance Testing: Dielectric properties were tested according to GB / T 5594.4-2015 (stripline method 20 GHz); bending strength was tested according to GB / T6569-2006; and sheet resistance of conductors was tested according to GB / T 17473.3-2008. The relative density of the ceramic substrate obtained in this embodiment was found to be 3.72 g / cm³. 3 The X / Y direction shrinkage rate is 15.3%, the Z direction shrinkage rate is 23.1%, the dielectric constant is 7.12, the dielectric loss is 0.0019, the bending strength is 405 MPa, and the sheet resistance is 6.5 mΩ / □. Local magnification of the conductor lines reveals (e.g.) Figure 2 As shown), the metallization layer is dense and uniform, and has a tight bond with the ceramic matrix interface. The ceramic matrix is microscopically dense (as shown). Figure 3 (As shown).
[0032] Example 2 (1) Preparation of sintering aid: Weigh 16 parts SiO2, 4 parts TiO2, 24 parts kaolin, 18 parts CaO, 9 parts NiO, 11 parts ZrO2, 11 parts Cr2O3, and 7 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.7 μm by a laser particle size analyzer.
[0033] (2) Preparation of raw ceramic powder: Weigh 91 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 9 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0034] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0035] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The substrate is co-fired in an atmosphere furnace at 1420 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0036] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The relative density of the ceramic substrate obtained in this example is 3.71 g / cm³. 3 The shrinkage rate in the X / Y direction is 15.1%, the shrinkage rate in the Z direction is 23.0%, the dielectric constant is 7.15, the dielectric loss is 0.0029, the flexural strength is 403 MPa, and the sheet resistance is 5.9 mΩ / □. Magnified observation of the conductor lines reveals that the metallization layer is dense and uniform, and tightly bonded to the ceramic substrate interface.
[0037] Example 3 (1) Preparation of sintering aid: Weigh 17 parts SiO2, 6 parts TiO2, 20 parts kaolin, 20 parts CaO, 10 parts NiO, 11 parts ZrO2, 10 parts Cr2O3, and 6 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0038] (2) Preparation of raw ceramic powder: Weigh 90 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 10 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0039] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0040] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0041] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The substrate obtained in this example has a ceramic relative density of 3.72 g / cm³, a shrinkage rate of 15.2% in the X / Y direction, a shrinkage rate of 23.0% in the Z direction, a dielectric constant of 7.31, a dielectric loss of 0.0023, a bending strength of 408 MPa, and a sheet resistance of 6.3 mΩ / □. Magnified observation of the conductor lines shows that the metallization layer is dense and uniform, and tightly bonded to the ceramic substrate interface.
[0042] Example 4 (1) Preparation of sintering aid: Weigh 15 parts SiO2, 6 parts TiO2, 25 parts kaolin, 18 parts CaO, 12 parts NiO, 8 parts ZrO2, 6 parts Cr2O3, and 10 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0043] (2) Preparation of raw ceramic powder: Weigh 88 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 12 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0044] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0045] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0046] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The substrate obtained in this example has a ceramic relative density of 3.70 g / cm³, a shrinkage rate of 15.1% in the X / Y direction, a shrinkage rate of 23.0% in the Z direction, a dielectric constant of 7.4, a dielectric loss of 0.0028, a bending strength of 401 MPa, and a sheet resistance of 6.4 mΩ / □. Magnified observation of the conductor lines shows that the metallization layer is dense and uniform, and tightly bonded to the ceramic substrate interface.
[0047] Example 5 (1) Preparation of sintering aid: Weigh 15 parts SiO2, 3 parts TiO2, 21 parts kaolin, 20 parts CaO, 15 parts NiO, 8 parts ZrO2, 8 parts Cr2O3, and 10 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.5 μm by a laser particle size analyzer.
[0048] (2) Preparation of raw ceramic powder: Weigh 88 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 12 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0049] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0050] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1400 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0051] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The substrate obtained in this example has a ceramic relative density of 3.72 g / cm³, a shrinkage rate of 15.4% in the X / Y direction, a shrinkage rate of 23.1% in the Z direction, a dielectric constant of 7.1, a dielectric loss of 0.0027, a bending strength of 404 MPa, and a sheet resistance of 5.8 mΩ / □. Magnified observation of the conductor lines shows that the metallization layer is dense and uniform, and tightly bonded to the ceramic substrate interface.
[0052] Comparative Example 1 (1) Preparation of raw ceramic powder: Weigh 100 parts of alumina powder (purity ≥99.9%, D50=0.7μm), place them in a mixer and mix thoroughly to obtain inorganic ceramic powder.
[0053] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0054] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0055] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The obtained sample could not be ceramicized after sintering at 1450℃, had a loose structure, and the relative density of the ceramic was 2.42 g / cm³. 3 The dielectric constant, dielectric loss, flexural strength, and sheet resistance could not be tested. This indicates that without the sintering aid of the present invention, the alumina ceramic could not be densified under the stated sintering conditions, highlighting the necessity of the sintering aid of the present invention.
[0056] Comparative Example 2 (1) Preparation of sintering aid: Weigh 60 parts of SiO2, 30 parts of CaO, and 10 parts of MgO. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0057] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0058] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0059] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0060] All tests were conducted according to the test standards / methods of Example 1. The test results are as follows: the relative density of the ceramic is 3.32 g / cm³. 3The shrinkage rate in the X / Y direction is 13.1%, the shrinkage rate in the Z direction is 18.4%, the dielectric constant is 9.2, the dielectric loss is 0.005, the flexural strength is 280 MPa, and the sheet resistance is 18 mΩ / □ (partial loss of copper phase after co-firing of tungsten-copper paste). This indicates that conventional sintering aids cannot achieve sufficient densification at 1450℃, resulting in low flexural strength and inability to effectively match the co-firing of tungsten-copper paste, further highlighting the technical advantages of the specific sintering aid system of this invention.
[0061] Comparative Example 3 (1) Preparation of sintering aid: Weigh 8 parts of Y2O3 and place them in a planetary ball mill. Use anhydrous ethanol as solvent and alumina balls as medium. The mass ratio of ball to material is 2:1, and the mass ratio of powder to ethanol is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0062] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0063] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0064] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0065] All tests were conducted according to the testing standards / methods of Example 1. The resulting sample, after sintering at 1450℃, was not dense and had a rough surface. Following the testing standards / methods of Example 1, the relative density of the ceramic was measured to be 3.12 g / cm³. 3The shrinkage rate in the X / Y direction is 14.3%, the shrinkage rate in the Z direction is 19.2%, the dielectric constant is 8.5, the dielectric loss is 0.03, and the flexural strength is 114 MPa. This indicates that a single sintering aid cannot achieve sufficient densification at 1450℃, has low flexural strength, and cannot effectively match the co-firing of tungsten-copper slurry, further highlighting the technical advantages of the specific sintering aid system of this invention.
[0066] Comparative Example 4 (1) Preparation of sintering aid: Weigh 16 parts SiO2, 4 parts TiO2, 20 parts kaolin, 16 parts CaO, 19 parts NiO, 7 parts ZrO2, 8 parts Cr2O3, and 10 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0067] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0068] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0069] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0070] (5) Performance testing: All tests were conducted according to the testing standards / methods of Example 1. The relative density of the ceramic substrate obtained in this example is 3.42 g / cm³. 3The shrinkage rate in the X / Y direction is 14.4%, the shrinkage rate in the Z direction is 19.6%, the dielectric constant is 7.2, the dielectric loss is 0.0045, the flexural strength is 264 MPa, and the sheet resistance is 9.2 mΩ / □. Magnified observation of the conductor lines reveals that the metallization layer is dense and uniform, and tightly bonded to the ceramic substrate interface.
[0071] Comparative Example 5 (1) Preparation of sintering aid: Weigh 30 parts of SiO2, 35 parts of kaolin, 14 parts of CaO, 5 parts of MnO, 10 parts of Cr2O3, and 6 parts of Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 1.0 μm by a laser particle size analyzer.
[0072] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0073] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0074] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast into shape on a casting machine and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process.
[0075] (5) Co-fired at 1550 °C for 2 hours, followed by furnace cooling to obtain an alumina HTCC multilayer co-fired substrate. Referring to Example 1, the substrate obtained in this example has a ceramic relative density of 3.74 g / cm³. 3The material exhibits a shrinkage rate of 15.7% in the X / Y direction and 23.4% in the Z direction, with a dielectric constant of 9.4, a dielectric loss of 0.0018, a flexural strength of 430 MPa, and a sheet resistance of 62.8 mΩ / □. The metallized layer is loose, and almost all the copper phase is lost after co-firing with the tungsten-copper paste. When co-fired in a furnace at 1450 ℃ for 4 hours, the resulting ceramic is not dense and has a rough surface. The measured dielectric constant is 8.7, the dielectric loss is 0.03, and the flexural strength is 110 MPa. This indicates that conventional HTCC sintering aids cannot achieve sufficient densification at 1450 ℃, resulting in low flexural strength and ineffective compatibility with tungsten-copper paste co-firing.
[0076] Comparative Example 6 (1) Preparation of sintering aid: Same as step (1) in Example 1.
[0077] (2) Preparation of raw ceramic powder: Same as step (2) in Example 1.
[0078] (3) Preparation of casting slurry: Same as step (3) in Example 1.
[0079] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1500 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0080] All tests were conducted according to the test standards / methods of Example 1. The test results are as follows: the relative density of the ceramic is 3.73 g / cm³. 3 The shrinkage rate in the X / Y direction is 15.3%, the shrinkage rate in the Z direction is 23.0%, the dielectric constant is 9.2, the dielectric constant is 7.4, the dielectric loss is 0.0015, the bending strength is 442MPa, and the sheet resistance is 26.5mΩ / □ (the copper phase is partially lost after the tungsten copper slurry is co-fired).
[0081] Comparative Example 7 (1) Preparation of sintering aid: Weigh 17 parts SiO2, 5 parts TiO2, 24 parts kaolin, 18 parts CaO, 7 parts NiO, 9 parts ZrO2, 10 parts Cr2O3, and 10 parts Y2O3. Place the above powders in a planetary ball mill, using anhydrous ethanol as solvent and alumina balls as medium. The ball-to-powder mass ratio is 2:1, and the powder-to-ethanol mass ratio is 1:1. Mix at 50 r / min for 4 hours. After separating the grinding balls by sieving, dry the resulting slurry at 80 ℃ for 12 hours to obtain the sintering aid powder. The D50 of the powder was measured to be 0.6 μm by a laser particle size analyzer.
[0082] (2) Preparation of raw ceramic powder: Weigh 92 parts of alumina powder (purity ≥99.9%, D50=0.7μm) and 8 parts of sintering aid powder obtained in step (1), and mix them thoroughly in a mixer to obtain inorganic ceramic powder.
[0083] (3) Preparation of casting slurry: Weigh 100 parts of the above inorganic ceramic powder, add 1 part of dispersant herring oil, 2 parts of plasticizer dibutyl phthalate, and 40 parts of solvent (anhydrous ethanol: methyl ethyl ketone mass ratio = 1:1), and place in a planetary ball mill and ball mill at 200 r / min for 1 hour. Then add 33 parts of a pre-prepared 30% PVB anhydrous ethanol-methyl ethyl ketone solution (containing about 10 parts PVB), and continue ball milling for 2 hours. Filter to remove the grinding balls, and vacuum degas the obtained slurry for 30 minutes to obtain the casting slurry.
[0084] (4) Casting, stacking, printing and co-firing: The above-mentioned casting paste is cast and shaped on a casting machine, and dried to obtain green ceramic sheets. The green ceramic sheets are stacked, isostatically pressed and cut, and then tungsten copper conductor paste is printed by screen printing process. The mixture is co-fired in an atmosphere furnace at 1450 ℃ for 4 hours. After cooling in the furnace, alumina MTCC multilayer co-fired substrate is obtained.
[0085] (5) Performance testing: All tests were conducted in accordance with the test standards / methods of Example 1. The substrate obtained in this example has a ceramic relative density of 3.63 g / cm³, a shrinkage rate of 14.3% in the X / Y direction, a shrinkage rate of 19.3% in the Z direction, a dielectric constant of 7.1, a dielectric loss of 0.0035, a bending strength of 334 MPa, and a sheet resistance of 7.2 mΩ / □.
[0086] Analysis of the test results above shows that, in Examples 1-5, sintering at a relatively low temperature of 1400-1450℃ resulted in a relative density of 3.70 g / cm³. 3 The flexural strength remained stable between 401-408 MPa, fully meeting the stringent mechanical reliability requirements of ceramic substrates. Comparative Example 1 failed to form ceramic at 1450℃, demonstrating the necessity of the additives in this invention. Comparative Examples 2-4 and 7, using other additive systems or non-preferred ratios, exhibited significantly lower relative densities and flexural strengths than the examples, even at the same or higher temperatures, indicating that the specific multi-component composite additives of this invention are key to achieving low-temperature densification.
[0087] Secondly, the metallized circuit sheet resistance of the substrates obtained in Examples 1-5 is extremely low, only 5.8-6.5 mΩ / □, and there is no loss of copper phase. This proves that the present invention achieves perfect matching and co-firing of alumina ceramic and tungsten copper paste at low temperature. When the sintering temperature of Comparative Examples 5 and 6 is increased to 1550℃ or 1500℃, although the substrate strength increases, the sheet resistance rises sharply to 62.8 mΩ / □ and 26.5 mΩ / □ (a large amount of copper phase is lost), which is an inherent defect of the HTCC process that the present invention strives to avoid. The sheet resistance of Comparative Example 2 (18 mΩ / □) is also significantly higher than that of the examples, and its copper phase is partially lost, confirming that non-inventive solutions cannot be effectively compatible with copper-based pastes at low temperatures.
[0088] In the examples, the proportions of the sintering aids were all within the preferred component ratio range of this invention (e.g., NiO 9-15%, ZrO2 8-11%), achieving excellent overall performance. However, Comparative Examples 4 (NiO 19%, ZrO2 7%) and 7 (NiO 7%) deviated from the preferred range. The results showed that the flexural strength of Comparative Example 4 decreased to 264 MPa, and the loss increased to 0.0045; the flexural strength and density of Comparative Example 7 were significantly lower than those of the examples. This indicates that the synergistic effect of NiO and ZrO2 depends on precise proportions, and deviations from this range significantly degrade material properties.
[0089] Comparative Example 3 used only Y₂O₃ as an auxiliary agent, and the sample was severely non-dense (relative density 3.12 g / cm³). 3 The strength is only 114 MPa, indicating that the octagonal composite additive system of the present invention achieves sintering promotion and performance optimization effects that cannot be achieved by a single component through multi-component synergistic effect.
[0090] In summary, compared to Comparative Examples 1-4 and 7, this invention achieves high densification and higher flexural strength (>400 MPa) at the same or lower temperatures, while ensuring lower dielectric loss and lower conductor sheet resistance. Compared to Comparative Examples 5-6 (traditional HTCC route), this invention maintains excellent mechanical and dielectric properties while lowering the sintering temperature by 100-150℃, thereby achieving co-firing with highly conductive tungsten copper paste and reducing sheet resistance by more than 80%, which is the most significant advancement of this invention.
[0091] Explanation of the tungsten-copper co-firing mechanism: The densification temperature range of alumina ceramics is controlled within 1400~1450℃ using an octa-component composite additive system. Within this temperature range, on the one hand, the amount of liquid phase generated by the additive system is moderate, sufficient to promote Al2O3 grain rearrangement and densification; on the other hand, the viscosity and surface tension characteristics of the liquid phase ensure that the tungsten skeleton maintains structural integrity during sintering, and the copper phase fully fills the pores of the tungsten skeleton and completes densification under capillary force. If the sintering temperature is below 1400℃, the ceramic matrix densification is insufficient, and the copper phase cannot obtain sufficient sintering driving force; if it is above 1450℃, the copper phase begins to melt and flow away, and the tungsten skeleton undergoes excessive sintering shrinkage, resulting in a sharp increase in sheet resistance (e.g., in Comparative Example 5, almost all copper is lost at 1550℃, resulting in a sheet resistance as high as 62.8 mΩ / □). The additive system described in this scheme simultaneously satisfies the two conditions of ceramic densification and low-temperature densification of the copper phase within the 1400~1450℃ window, achieving synchronous matching of ceramic-metal thermal behavior.
[0092] Although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
[0093] Therefore, the above description is only a preferred embodiment of this application and is not intended to limit the scope of this application; that is, all equivalent modifications made in accordance with the scope of the claims of this application shall be within the protection scope of the claims of this application.
Claims
1. An alumina MTCC green ceramic sheet, characterized in that, The green ceramic sheet is used for co-firing with tungsten-copper conductor slurry; the inorganic ceramic powder of the green ceramic sheet is composed of alumina powder and sintering aids; the sintering aids are composed of SiO2, TiO2, kaolin, CaO, NiO, ZrO2, Cr2O3 and Y2O3; the sintering aids account for 8% to 12% of the total mass of the inorganic ceramic powder. The sintering aid comprises the following components by mass percentage: SiO2 15%~17%, TiO2 3%~6%, Kaolin 20%–25%, CaO 16%~20%, NiO 9%~15%, ZrO2 8%~11%, Cr2O3 6%~11%, Y2O 36%~10%; The raw ceramic slabs are sintered and densified at 1400–1450°C.
2. The alumina MTCC green ceramic sheet according to claim 1, characterized in that, The alumina powder has a purity of ≥99.9% and an average particle size of 0.5–1 μm.
3. The alumina MTCC green ceramic sheet according to claim 1, characterized in that, It is obtained by casting the inorganic ceramic powder and the organic carrier; the organic carrier includes a solvent, a binder, a plasticizer and a dispersant; in the casting slurry, the inorganic ceramic powder accounts for 50% to 60% by mass, the binder accounts for 5% to 10% by mass, the solvent accounts for 30% to 40% by mass, the dispersant accounts for 0.5% to 1% by mass, and the plasticizer accounts for 1% to 3% by mass.
4. The alumina MTCC green ceramic sheet according to claim 3, characterized in that, The binder is polyvinyl butyral, the solvent is a mixture of anhydrous ethanol and methyl ethyl ketone, the dispersant is herring oil or Span 80, and the plasticizer is dibutyl phthalate.
5. The method for preparing alumina MTCC green ceramic sheets as described in claim 3, characterized in that, Includes the following steps: (1) Weigh SiO2, TiO2, kaolin, CaO, NiO, ZrO2, Cr2O3 and Y2O3, mix them, add anhydrous ethanol, grind and dry to obtain sintering aid powder; (2) The sintering aid powder is mixed with alumina powder to obtain the inorganic ceramic powder; (3) The inorganic ceramic powder is mixed and ground with the solvent and dispersant, and then the binder and plasticizer are added and ground again to obtain the casting slurry; the solid content of the casting slurry is 50% to 60%; (4) After degassing the cast slurry, it is cast and dried to obtain the alumina medium-temperature co-fired ceramic green ceramic sheet.
6. The use of alumina MTCC green ceramic sheet as described in any one of claims 1-4 in the preparation of ceramic substrates co-fired with tungsten copper conductor paste.
7. An alumina medium-temperature co-fired ceramic substrate, characterized in that, It is obtained by sintering alumina MTCC green ceramic sheets according to any one of claims 1-4 at 1400-1450°C.
8. The alumina medium-temperature co-fired ceramic substrate according to claim 7, characterized in that, The substrate has a bending strength ≥400MPa, a dielectric constant of 7.0~7.5, and a dielectric loss ≤0.
003.
9. The alumina medium-temperature co-fired ceramic substrate according to claim 7, characterized in that, After the substrate is co-fired with the tungsten copper conductor paste, the sheet resistance of the metallized circuit is ≤7mΩ / □.
Citation Information
Patent Citations
Aluminium nitride ceramic substrate, and preparation method thereof
CN107188568A
A high-dielectric-constant microwave dielectric ceramic material sintered at a low temperature, and a preparing method and applications thereof
CN108033785A
Method, sintering aid and materials for preparation of low-temperature cofired medium ceramic and application
CN102863221A
Binding phase for tungsten-copper electronic paste and preparation method thereof
CN119551970A
